Deictic Expressions in the First SONAs of Rodrigo Duterte and Ferdinand Marcos Jr. - Ma. Sophia Pintado; Mark Jayce Cereño; Annalie Librea; Rechie Bejasa; Joemar Turno Minoza (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This study assumes that former President Rodrigo Duterte and President Ferdinand Marcos Jr. used different types of deixis in their first State of the Nation Address (SONAs). Supporting this assumption is the theory of Deictic Expressions by Stephen Levinson. This study is descriptive qualitative. Findings revealed that former President Duterte and President Marcos Jr. used different types of deixis in their speeches. The most dominant type of deixis used by former President Duterte is personal deixis, which obtained the highest frequency, particularly the pronoun "I". In contrast, the most prevalent deixis used by President Marcos is "personal deixis", particularly the pronoun "we". It is concluded that personal deixis was the most dominant type of deixis among the five types used by the two speakers in their speeches. Future researchers are encouraged to conduct a future study that will focus on the usage of deixis in books or speeches.